(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
This study aimed to evaluate the effectiveness of botulinum toxin (Botox) type A injections in patients with temporomandibular disorders TMD, where the research sample consisted of 14 symptoms of myofascial pain MFP, Faculty of Dentistry, Tishreen University. They were treated with Botox injections into the masticatory muscle in the outer part of the muscle from outside the mouth and the inner part inside the oral fossa. The results were monitored three months after the injection, and the rate of the mouth opening, the lateral movements of the lower jaw, the rate of pain felt by the patient upon muscular palpation, and the patient’s amount of pain were recorded according to the visual analog scale VAS.The results showed a decrease in the degree of pain on palpation after a month by 100%, and its absence after 3 months, and it was also noted that p-value<0.05, and accordingly, there are significant statistically differences between the degree of pain on palpation during the observation period. We also found a greater improvement in the sample after three months of observation for the opening of the mouth movements and lateral movements with a statistically significant difference, as the pain decreased according to the VAS. Conclusion: Within the limits of this study, Botox was shown to be effective in treating myofascial pain associated with temporomandibular disorders. Therefore, we recommend using Botox injections as a quick and immediate way to treat temporomandibular disorders.